The Effect of Price, Promotion, and Product Innovation on Grab Car Customer Satisfaction - Heryanti, Heryanti; Subarjo, Subarjo (Universitas Negeri Yogyakarta, 2025)
This study aims to analyze the effect of Price, Promotion, and Product Innovation on Customer Satisfaction. The research was conducted on 100 respondents selected using purposive sampling methods. Data were collected through questionnaires and analyzed using statistical methods, including validity tests, reliability tests, and multiple linear regression analysis. The results of the study indicate that all three independent variables, namely Price, Promotion, and Product Innovation, have a significant effect simultaneously on Customer Satisfaction. Partially, Promotion contributes the most dominant influence on customer satisfaction, followed by Product Innovation, while Price has a smaller but still significant effect. This study also demonstrates that Customer Satisfaction can be significantly enhanced through effective promotional strategies, relevant product innovations that meet market needs, and competitive pricing. This research provides practical recommendations for business practitioners to focus on strategic promotion and sustainable product innovation, as well as the importance of considering price management that aligns with market values. This study has limitations in terms of sample size and the focus on the variables used, thus, future research is suggested to expand the scope of variables and increase the number of respondents.